Problematika guru dalam menghadapi perubahan kurikukum: Analisis kesulitan guru pada penerapan kurikulum merdeka - Zainuddin, Zainuddin (Maliki Interdisciplinary Journal, 2024)
It is hoped that the independent curriculum will become an education system that will change the post-coronavirus educational environment. Online-based learning requires students to study remotely via the Zoom platform, Google Classroom, Google Meet, etc. The existence of a voluntary curriculum as a mechanism to improve the post-corona situation and encourage learning through a voluntary curriculum. An independent curriculum gives teachers the freedom to determine learning models, learning media and learning strategies that are adapted to the context and conditions of students in the class. However, in an education system with an independent curriculum, teachers face challenges in managing changes to the independent curriculum. Teachers experience these obstacles when implementing their own curriculum. This research method uses the berry-picking method to search for topics being discussed in several journal databases such as Google Scholar, and uses the method to check and cite references in articles. The search used published articles, scientific community and journal identification. Typically, you will publish the topic you are researching and check the abstracts and bibliographic database indexes. The results of this research are "Teachers’ Problems When Facing Curriculum Changes. The Teachers difficulties in implementing their own curriculum are analyzed as follows. Managing learning devices can be troublesome for teachers, due to lack of experience with independent learning curricula, limited materials and modules, and lack of equipment and infrastructure to implement independent learning curricula.